2016
DOI: 10.1136/thoraxjnl-2016-209333.135
|View full text |Cite
|
Sign up to set email alerts
|

S129 What proportion of patients with lung cancer would have been eligible for ct screening according to various proposed inclusion criteria?

Abstract: The US National Lung Screening Trial (NLST) identified persons for lung cancer screening by age (55–74 yrs) and smoking history, but a subsequent analysis of the US SEER database showed that only 26.7% of lung cancer cases would have been eligible for screening according to these criteria.Strategies to increase the proportion of lung cancer patients who might qualify for screening include increasing the upper age limit to 80 years (endorsed by the US Preventative Services Task Force – USPSTF), and using compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Despite the evidence in mortality reduction among the heavy smokers, the question on how to best identify the target population for screening remains open. Multiple studies showed that only approximately 20% to 30% of LC patients would have been eligible for screening with NLST criteria, meaning that 70% to 80% of LC would be missed by screening 27‐36 . LC screening recommendations in the United States are now in the process to be changed to screen a larger proportion of the population that might reduce the number of potentially missed LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evidence in mortality reduction among the heavy smokers, the question on how to best identify the target population for screening remains open. Multiple studies showed that only approximately 20% to 30% of LC patients would have been eligible for screening with NLST criteria, meaning that 70% to 80% of LC would be missed by screening 27‐36 . LC screening recommendations in the United States are now in the process to be changed to screen a larger proportion of the population that might reduce the number of potentially missed LC.…”
Section: Discussionmentioning
confidence: 99%
“…for screening with NLST criteria, meaning that 70% to 80% of LC would be missed by screening. [27][28][29][30][31][32][33][34][35][36] LC screening recommendations in the United States are now in the process to be changed to screen a larger proportion of the population that might reduce the number of potentially missed LC. The new suggested recommendation lowered the bar for both age (starting at 50 instead of 55 years) and the smoking history (at least 20 instead of 30 required pack-year history).…”
Section: Prevalence Of Preclinical Lc In the General Populationmentioning
confidence: 99%